11(t-4)+7t=6(3t+4)-12

Simple and best practice solution for 11(t-4)+7t=6(3t+4)-12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(t-4)+7t=6(3t+4)-12 equation:


Simplifying
11(t + -4) + 7t = 6(3t + 4) + -12

Reorder the terms:
11(-4 + t) + 7t = 6(3t + 4) + -12
(-4 * 11 + t * 11) + 7t = 6(3t + 4) + -12
(-44 + 11t) + 7t = 6(3t + 4) + -12

Combine like terms: 11t + 7t = 18t
-44 + 18t = 6(3t + 4) + -12

Reorder the terms:
-44 + 18t = 6(4 + 3t) + -12
-44 + 18t = (4 * 6 + 3t * 6) + -12
-44 + 18t = (24 + 18t) + -12

Reorder the terms:
-44 + 18t = 24 + -12 + 18t

Combine like terms: 24 + -12 = 12
-44 + 18t = 12 + 18t

Add '-18t' to each side of the equation.
-44 + 18t + -18t = 12 + 18t + -18t

Combine like terms: 18t + -18t = 0
-44 + 0 = 12 + 18t + -18t
-44 = 12 + 18t + -18t

Combine like terms: 18t + -18t = 0
-44 = 12 + 0
-44 = 12

Solving
-44 = 12

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 7=7b+4b | | 2w-6x-y+4w+18x-4y= | | 7(56+85)7x(57x+70)=30x | | -4(6y-9)-y=-4(y-4) | | 354+228= | | 5+(4x-12)=140 | | 5x(4x-12)=140 | | 12+11d=-18-4d | | -345+228= | | 5x-3y+8w+2y-2w+7x= | | x+2y=-63 | | 27x-x^2=180 | | x+(x+275000)=625000000 | | 135-6x=39x+15 | | 16r=64 | | 12x-43=5x+19 | | 2x+3x-7=38 | | 2r^2+r+6=0 | | 14x-(25-5x)=10+15 | | 2n-5n+11=2-3n+9 | | 4x+25=29 | | 2x+8+x=-12-2x | | -9k=2.34 | | y^4-25y^2+144=0 | | 4(4+3x)=136 | | 8x=48 | | 3(x-5)=3+x | | 12y-3=16y-9y | | 2Y+19=23 | | 4x^2-13x+7=8x+2 | | t^2+t=2 | | x^2+4x+p=0 |

Equations solver categories